Incidence of Undetectable, Measurable, and Increased Cardiac Troponin I Concentrations Above the 99th Percentile Using a High-Sensitivity vs a Contemporary Assay in Patients Presenting to the Emergency Department. (6th January 2020) - Love, Sara A; Sandoval, Yader; Smith, Stephen W; Nicholson, Jennifer; Cao, Jing; Ler, Ranka; Schulz, Karen; Apple, Fred S
Abstract: INTRODUCTION: We compared the incidence of undetectable [below the limit of detection (LoD)], measurable (LoD to 99th percentile), and increased cardiac troponin I (cTnI) concentrations above the 99th percentile between Abbott high-sensitivity cTnI (hs-cTnI) and contemporary cTnI assays in a US emergency department population. METHODS: Patients (n = 2100) presenting to the emergency department who had serial cTnI (0, 3, 6, 9 h) measurements ordered on clinical indication were enrolled. Contemporary cTnI [Abbott Architect used clinically; 99th percentile: 0.030 μg/L (30 ng/L)] and hs-cTnI [Abbott investigational; sex-specific 99th percentiles: female (F) 16 ng/L, male (M) 34 ng/L] assays simultaneously measured fresh EDTA plasma. RESULTS: The hs-cTnI assay measured fewer undetectable cTnI concentrations compared to the contemporary cTnI assay across baseline (F: 31% vs 47%, M: 22% vs 40%) and serial (F: 21% vs 46%; M: 19% vs 54%) measurements. Conversely, the proportion of measurable cTnI concentrations was higher using hs-cTnI compared to contemporary cTnI assay across both baseline (F: 46% vs 31%; M: 60% vs 33%) and serial (F: 48% vs 28%; M: 83% vs 40%) measurements. The overall proportion of patients with increased cTnI concentrations above the 99th percentile was not significantly different between the contemporary (31%) and hs-cTnI (26%) assays ( P = 0.09). CONCLUSIONS: In patients presenting to the emergency department, the use of the Abbott hs-cTnI assay provides clinicians with more numeric cTnI concentrations. This occurs via a shift from results below the LoD to those between the LoD and the 99th percentile and does not increase in the number of cTnI concentrations above the 99th percentile.